2009
DOI: 10.2166/wst.2009.489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microbial fuel cell coupled with aeration chamber and bio-cathode for organic matter and nitrogen removal from synthetic domestic wastewater

Abstract: For simultaneous carbon and nitrogen removal via single stream, a microbial fuel cell (MFC) coupled with an aeration chamber and a bio-cathode was investigated. Without catalysts and any additional buffer, the MFC produced electricity continuously and the power density reached 1.3 W/m3 at a loading rate of 1.6 kg COD/m3 d. Simultaneously, the COD and the nitrate removal rate were 1.4 kg COD/m3 d and 67 g NO3-N/m3 d, respectively. When the hydraulic retention time was changed from 6 to 0.75 hours, the power den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…However, the rate of TN removal was relatively slow. The explanation for this finding is that the nitrogen was mainly removed by electrochemical method at lower C/N wastewater and the rate of electrochemical denitrification was slower than that of heterotrophic denitrification . Hence, the tolerance of the system at 100 Ω was C/N = 1 with above 90% TN decrease.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the rate of TN removal was relatively slow. The explanation for this finding is that the nitrogen was mainly removed by electrochemical method at lower C/N wastewater and the rate of electrochemical denitrification was slower than that of heterotrophic denitrification . Hence, the tolerance of the system at 100 Ω was C/N = 1 with above 90% TN decrease.…”
Section: Resultsmentioning
confidence: 97%
“…The explanation for this finding is that the nitrogen was mainly removed by electrochemical method at lower C/N wastewater and the rate of electrochemical denitrification was slower than Enhanced nitrogen removal of low C/N wastewater www.soci.org that of heterotrophic denitrification. 24,[35][36][37] Hence, the tolerance of the system at 100 Ω was C/N = 1 with above 90% TN decrease. By calculating the organic matter and nitrogen values, the mole C/N ratio was lower than that of traditional membrane aerated biofilm reactor (MABR) (about C/N = 2.11) 38 and that of novel sludge system (about C/N = 1.70).…”
Section: Wileyonlinelibrarycom/jctbmentioning
confidence: 99%
“…The major N-containing compound after nitrate reduction was nitrogen gas with an electrode as direct electron donor in a biofilm-electrode reactor [24]. It was also reported that microbial fuel cell coupled with aeration chamber and biocathode converted 72% of nitrate to nitrite and the remaining might have been converted to nitrous oxide or nitrogen gas [25]. In this study, we assumed the rest of nitrate went to nitrogen gas; it would be 15.6 mg (N 2 -N) L −1 .…”
Section: Nitrate Removal On the Plain Carbon Electrodementioning
confidence: 99%
“…MFCs represent a potential alternative approach when compared to conventional activated sludge wastewater treatment systems because energy is produced in the form of electricity or hydrogen gas rather than using energy for aeration or for other treatment processes (Logan, 2008). The application of MFCs for wastewater treatment has been documented in many reports (Aelterman et al, 2006;Ahn and Logan, 2010;Cha et al, 2009; Kargi and Eker, 2007;Vidris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%